Heteroleptic Coordination Environments in Metal-Mediated DNA G-Quadruplexes - Punt, Philip M.; Stratmann, Lukas M.; Sevim, Sinem; Knauer, Lena; Strohmann, Carsten; Clever, Guido H. (Frontiers in Chemistry, 2020)
The presence of metal centers with often highly conserved coordination environments is crucial for roughly half of all proteins, having structural, regulatory or enzymatic function. To understand and mimic the function of metallo-enzymes, bioinorganic chemists pursue the challenge of synthesizing model compounds with well-defined, often heteroleptic metal sites. Recently, we reported the design of tailored homoleptic coordination environments for various transition metal cations based on unimolecular DNA G quadruplex structures, templating the regioselective positioning of imidazole ligandosides LI. Here, we expand this modular system to more complex, heteroleptic coordination environments by combining LI with a new benzoate ligandoside LB within the same oligonucleotide. The modifications still allow the correct folding of parallel tetramolecular and antiparallel unimolecular G-quadruplexes. Interestingly, the incorporation of LB results in strong destabilization expressed in lower thermal denaturation temperatures Tm. While no transition metal cations could be bound by G-quadruplexes containing only LB, heteroleptic derivatives containing both LI and LB were found to complex CuII, NiII and ZnII. Especially in case of CuII we found strong stabilizations of up to ΔTm = +34 °C. The here shown system represents an important step towards the design of more complex coordination environments inside DNA scaffolds, promising to culminate in the preparation of functional metallo-DNAzymes.